Wave impact loads on wave-piercing catamarans. (1st February 2017) - Lavroff, J.; Davis, M.R.; Holloway, D.S.; Thomas, G.A.; McVicar, J.J.
Abstract: Wave slamming is investigated for the 112 m INCAT wave-piercer catamaran with reference to experimental work conducted at full scale, numerical computation by CFD and FEA and testing at model scale using a 2.5 m segmented hydro-elastic model. The segmented model was tested in regular head seas to investigate the magnitude and location of the dynamic wave slam force and slam induced hull bending moments. The model consists of rigid segments joined by elastic hinges designed to match the scaled first longitudinal modal (whipping) frequency measured at full-scale on the INCAT 112 m vessel. Effects of forward speed and wave encounter frequency on slamming and whipping were investigated. Scaled slam forces of up to 2150 t weight (21.1 MN) were measured during model tests for a full-scale vessel with a loaded displacement of 2500 t. These slams can impart impulses on the bow of up to 938 t weight-seconds (9.20 MNs) and strain energy of up to 3.5 MJ into the ship structure based on scaled model test data. The impact energy is transferred primarily to the main longitudinal whipping mode, which decays with an overall structural damping ratio of 0.02–0.06, this being strongly dependent on internal frictional mechanisms within the ship structure. Highlights: Modes of vibration are investigated through ship measurements and FEA. A 2.5 m model was developed based on the 112 m INCAT catamaran. Towing tank tests were performed to measure slam loads and bending moments. Model data is shown to provide a good basis for validating numerical simulations. Slam loads measured are found to approach the total mass of model.